2013
DOI: 10.1161/hypertensionaha.111.01047
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure in Treated Hypertensive Individuals With the MTHFR 677TT Genotype Is Responsive to Intervention With Riboflavin

Abstract: The frequency of the homozygous mutant MTHFR 677TT genotype is reported to be 10% worldwide, ranging from 4% to 18% in the United States, 20% in northern China to as high as 32% in Mexico. 12 The MTHFR enzyme catalyzes the conversion of 5, 10-methylenetetrahydrofolate into 5-methyltetrahydrofolate which, in turn, is required for the remethylation of homocysteine to methionine. The common 677C→T variant in MTHFR results in a thermolabile enzyme with decreased activity, typically leading to elevated plasma homoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 33 publications
7
91
0
Order By: Relevance
“…At baseline, 60% of the participants had failed to achieve target BP levels (≤140/90 mmHg), despite taking three or more antihypertensive medications. Following riboflavin intervention (1·6 mg/d for 16 weeks), systolic BP decreased significantly, a finding which confirmed that the BP-lowering effects of riboflavin in individuals with the MTHFR 677TT genotype were not confined to high-risk CVD patients but also applied to hypertensive individuals generally (51) .…”
Section: Mthfr 677c T Polymorphism and Blood Pressuresupporting
confidence: 57%
See 1 more Smart Citation
“…At baseline, 60% of the participants had failed to achieve target BP levels (≤140/90 mmHg), despite taking three or more antihypertensive medications. Following riboflavin intervention (1·6 mg/d for 16 weeks), systolic BP decreased significantly, a finding which confirmed that the BP-lowering effects of riboflavin in individuals with the MTHFR 677TT genotype were not confined to high-risk CVD patients but also applied to hypertensive individuals generally (51) .…”
Section: Mthfr 677c T Polymorphism and Blood Pressuresupporting
confidence: 57%
“…Given the known metabolic interdependencies between the relevant B-vitamins, work is underway at this Centre to investigate the independent and combined effects of riboflavin and folic acid on BP in hypertensive individuals with the TT genotype in a factorial study design. In addition, although convincing evidence has demonstrated the BP-lowering effects of low-dose riboflavin over a relatively short period of time (1·6 mg/16 weeks) (49)(50)(51) , it remains to be seen how variations in dose and duration would influence the BP-lowering effects of riboflavin in these genetically at-risk patients.…”
Section: Mthfr 677c T Polymorphism and Blood Pressurementioning
confidence: 99%
“…Homozygosity (MTHFR 677TT genotype) for a common polymorphism in MTHFR, affecting over 10 % of the UK and Irish populations and up to 32 % of other populations worldwide (2) , has been associated with an increased risk of CVD (3) and more recently with hypertension (4) . Emerging evidence from intervention trials supports a novel role for riboflavin supplementation in protecting against hypertension specifically in individuals with the MTHFR 677TT genotype (5)(6)(7) . This genotypespecific effect of riboflavin potentially offers a personalised approach for the prevention and treatment of *Corresponding author: Professor M. Ward, email mw.ward@ulster.ac.uk…”
mentioning
confidence: 99%
“…Hypertension and response to riboflavin [44,45] IsoP F2-isoprostanes † Risk of renal failure in hypertensives and cardiovascular risk [55,56] MPO Myeloperoxidase † , rs2333227…”
Section: Prkca Rs16960228mentioning
confidence: 99%
“…This raises the distinct possibility of using this or similar biomarkers, in personalized dietary programs and as a monitoring tool for dietary intake, including the use of functional foods, listed in Table 2 [43]. The MTHFR 677TT (rs1801133) variant is of particular interest in nutrigenomics as the folate pathway is modified with the administration vitamin B2 (riboflavin) [44,45]. A randomized trial, using genomic enrichment for hypertensive patients with the TT genotype, has shown that blood pressure can be reduced by approximately 6 mmHg systolic with administration of riboflavin [45].…”
Section: Metabolomics the Gut Microbiome And Nutrigeneticsmentioning
confidence: 99%